2016
DOI: 10.1038/srep20121
|View full text |Cite
|
Sign up to set email alerts
|

H19 activates Wnt signaling and promotes osteoblast differentiation by functioning as a competing endogenous RNA

Abstract: Bone homeostasis is tightly orchestrated and maintained by the balance between osteoblasts and osteoclasts. Recent studies have greatly expanded our understanding of the molecular mechanisms of cellular differentiation. However, the functional roles of non-coding RNAs particularly lncRNAs in remodeling bone architecture remain elusive. In our study, lncRNA H19 was found to be upregulated during osteogenesis in hMSCs. Stable expression of H19 significantly accelerated in vivo and in vitro osteoblast differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
217
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(229 citation statements)
references
References 41 publications
10
217
1
1
Order By: Relevance
“…The authors argued that this might be due to the negative-feedback loop associated with H19 and miR-675-5p. Meanwhile, they revealed another mechanism for H19 in the enhancement of osteogenic differentiation of BMSCs that concerned H19 -mediated activation of Wnt signaling by acting as a microRNA sponge for miR-141 and miR-22, both of which negatively regulated β-catenin [20]. Here, we found that H19 expression decreased significantly during osteogenic differentiation of human ASCs.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The authors argued that this might be due to the negative-feedback loop associated with H19 and miR-675-5p. Meanwhile, they revealed another mechanism for H19 in the enhancement of osteogenic differentiation of BMSCs that concerned H19 -mediated activation of Wnt signaling by acting as a microRNA sponge for miR-141 and miR-22, both of which negatively regulated β-catenin [20]. Here, we found that H19 expression decreased significantly during osteogenic differentiation of human ASCs.…”
Section: Discussionmentioning
confidence: 49%
“…The expression of H19 , which is upregulated and exhibits functions involved in osteogenic differentiation of human BMSCs [16, 18, 20], was decreased (Fold change: 3.81) in osteogenic differentiated ASCs as compared with undifferentiated cells according to our microarray results. To validate the differences in these results and explore the possible function of H19 in ASCs, we measured dynamic H19 expression during osteogenic processes of human ASCs and examined the effect of H19 knockdown on osteogenesis of human ASCs.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The significance of this upregulation is currently unclear. Since H19 was shown to play an important role in adult stem cell maintenance (71,72) and also activates Wnt signaling by upregulation of β -catenin (73), it is possible that this H19 upregulation may be associated with the observed MSC-like phenotype of MNCs. Intriguingly, there is a subset of miRNAs that are perfectly anti-correlated to the expression of their primary lncRNA.…”
Section: Discussionmentioning
confidence: 99%
“…A similar function in stabilizing SREBP-1c and promoting lipogenesis has been described for lncRNA H19, which like MALAT1, is upregulated by fatty acids [26 ■ ]. H19 was originally reported to function as a protein scaffold in tumor development and osteoblast differentiation [27,28]. Further study showed that in hepatocytes H19 alters SREBP-1c activity at both the mRNA and protein levels.…”
Section: Long Noncoding Rnas Regulating the Sterol Regulatory Elementmentioning
confidence: 99%